Standard CBT versus integrative and multimodal CBT assisted by virtual-reality for generalized anxiety disorder - Popa, Cosmin Octavian; Sava, Florin Alin; Muresan, Simona; Schenk, Alina; Cojocaru, Cristiana Manuela; Muntean, Lorena Mihaela; Olah, Peter (Frontiers in Psychology, 2022)
Introduction: Generalized Anxiety Disorder (GAD) is a prevalent emotional disorder associated with increased dysfunctionality, which has a lasting impact on the individual’s quality of life. Besides medication, Cognitive-Behavioral Therapy (CBT) represents the golden standard psychotherapeutic approach for GAD, integrating multilevel techniques and various delivery formats that enable the development of tailored treatment protocols. The objective of this study was to compare the efficiency of a standard CBT protocol targeting worries, dysfunctional beliefs, and intolerance of uncertainty with an integrative and multimodal CBT intervention augmented with Virtual Reality (VR). Materials and Methods: This study included 66 participants (Mage=22.53 years; SD = 2.21) with moderate GAD symptoms that were randomized to the standard CBT group (CBTs; N=32) and the Integrative and Multimodal CBT augmented with VR (IM-VRCBT; N=34) group. The interventions comprised 10 weekly sessions conducted by trained CBT therapists, including cognitive restructuring, problem-solving, behavioral exposure, and relaxation techniques. Baseline and post-assessments were conducted with both groups. Primary outcome measures included the Hamilton Anxiety Rating Scale (HARS) and Penn-State Worry Questionnaire (PSWQ) to evaluate the severity of GAD symptoms and worries respectively. Secondary outcomes involved the administration of Automatic Thoughts Questionnaire (ATQ), Dysfunctional Attitudes Scale (DAS) and Unconditional Self-Acceptance Questionnaire (USAQ). Results: Both interventions determined statistically significant effects on both primary and secondary outcomes (ps < .001) in the expected direction. However, CBTs was associated with higher effect sizes for anxiety (Cohen’s d=2.76) and worries (Cohen’s d=1.85), in contrast to IM-VRCBT. Also, secondary analyses revealed positive correlations between changes in anxiety and worries level and the reduction of dysfunctional cognitive processes. Conclusion: This research emphasized the effectiveness of CBT interventions for treating adults with moderate GAD symptomatology. Specifically, both interventions were efficient for reducing anxiety symptomatology present at individuals with GAD. However, regarding cognitive dysfunctions like worries, the standard CBT protocol performed better, as compared to the IM-VRCBT. In addition, we conclude that VR could be integrated within CBT interventions in a single protocol for GAD treatment.